Heterologous Combination of VSV-GP and NYVAC Vectors Expressing HIV-1 Trimeric gp145 Env as Vaccination Strategy to Induce Balanced B and T Cell Immune Responses - Perdiguero, Beatriz; Gómez, Carmen Elena; García-Arriaza, Juan; Sánchez-Corzo, Cristina; Sorzano, Carlos Óscar S.; Wilmschen, Sarah; von Laer, Dorothee; Asbach, Benedikt; Schmalzl, Christina; Peterhoff, David; Ding, Song; Wagner, Ralf; et al. (Frontiers in Immunology, 2019)
The generation of a vaccine against HIV-1 able to induce durable protective immunity continues a major challenge. The modest efficacy (31.2%) of the phase III RV144 clinical trial provided the first demonstration that a prophylactic HIV/AIDS vaccine is achievable but emphasized the need for further refinements of vaccine candidates, formulations, and immunization regimens. Here, we analyzed in mice the immunogenicity profile elicited by different homologous and heterologous prime/boost combinations using the modified rhabdovirus VSV-GP combined with DNA or poxviral NYVAC vectors, all expressing trimeric membrane-bound Env (gp145) of HIV-1 96ZM651 clade C, with or without purified gp140 protein component. In cultured cells infected with recombinant VSV-GP or NYVAC viruses, gp145 epitopes at the plasma membrane were recognized by human HIV-1 broadly neutralizing antibodies (bNAbs). In immunized mice, the heterologous combination of VSV-GP and NYVAC recombinant vectors improved the induction of HIV-1 Env-specific humoral and cellular immune responses compared to homologous prime/boost protocols. Specifically, the combination of VSV-GP in the prime and NYVAC in the boost induced higher HIV-1 Env-specific T cell (CD4/CD8 T cells and T follicular helper -Tfh- cells) immune responses compared to the use of DNA or NYVAC vectors in the prime and VSV-GP in the boost. Such enhanced T cell responses correlated with an enhancement of the Env-specific germinal center (GC) B cell population and with a heavily biased Env-specific response toward the Th1-associated IgG2a and IgG3 subclasses, while the other groups showed a Th2-associated IgG1 bias. In summary, our T and B cell population data demonstrated that VSV-GP-based vectors could be taken into consideration as an optimized immunogenic HIV-1 vaccine candidate component against HIV-1 when used for priming in heterologous combinations with the poxvirus vector NYVAC as a boost.